Barriers Affecting the Effectiveness of Digital Literacy Training Programs (DLTPs) for Marginalised Populations: A Systematic Literature Review - Choudhary, Heena; Bansal, Nidhi (Journal of Technical Education and Training, 2022)
The governments and private sectors have taken several national or regional digital literacy training programs (DLTPs) to mitigate digital inequalities. However, there are noticeable differences in impact and outcomes produced by programs. Since digital literacy is essential for any technical vocational education and training (TVET), this study explores possible barriers influencing the effectiveness of DLTPs at different level levels. Relevant publications were synthesized and coded using a systematic literature review to link main research findings with specific barrier categories. It was found that at the administrative level, policy planning and administrative designing, whereas at the training level, infrastructure followed by training and pedagogy emerged as the most critical determinants for the effectiveness of DLTPs. At an individual level, lack of family support significantly affects learning behavior. A strategic model for the effective implementation of DLTPs is provided. This study constitutes an essential input for research on the digital literacy training literature providing educators and program stakeholders with a reinforced understanding of various ways to manage DLTPs at different levels. Consequently, it closes some identified knowledge gaps and offers additional insights to improve the DLTPs performance at the community level.